2016
DOI: 10.1186/s12967-016-0852-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of BRAF V600 mutant circulating cell-free tumor DNA as a tool for therapeutic monitoring in metastatic melanoma patients treated with BRAF/MEK inhibitors

Abstract: BackgroundBRAF V600 mutant circulating cell-free tumor DNA (BRAF V600mut ctDNA) could serve as a specific biomarker in patients with BRAF V600 mutant melanoma. We analyzed the value of BRAF V600mut ctDNA from plasma as a monitoring tool for advanced melanoma patients treated with BRAF/MEK inhibitors.MethodsAllele-specific quantitative PCR analysis for BRAF V600 E/E2/D/K/R/M mutations was performed on DNA extracted from plasma of patients with known BRAF V600 mutant melanoma who were treated with dabrafenib and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 39 publications
7
117
3
3
Order By: Relevance
“…Transfection with miR-301a/inhibitor allowed for significant inhibition of tumor growth. The study indicated that miR-301a may act as a potential target in treatment of malignant melanoma [21].…”
Section: Leczenie Ukierunkowane Molekularniementioning
confidence: 95%
See 1 more Smart Citation
“…Transfection with miR-301a/inhibitor allowed for significant inhibition of tumor growth. The study indicated that miR-301a may act as a potential target in treatment of malignant melanoma [21].…”
Section: Leczenie Ukierunkowane Molekularniementioning
confidence: 95%
“…Transfekcja inhibitorem miR-301a pozwoliła na uzyskanie istotnego zahamowania progresji nowotworu. W badaniu stwierdzono, że rolę potencjalnego celu leczenia czerniaka może odgrywać miR-301a [21].…”
Section: Acquisition Of Resistance In General Treatmentunclassified
“…Of note, in this study, the well-established LDH had no impact on PFS. Other groups did not find a prognostic value of pre-treatment detection of BRAF-mutant ctDNA [33,[37][38][39]. Liquid biopsy studies on BRAF V600-mutant ctDNA without data on corresponding BRAF status in tumor tissue need to be interpreted with caution [28].…”
Section: Liquid Biopsy Modalities and Their Clinical Application In Amentioning
confidence: 98%
“…Liquid biopsy studies on BRAF V600-mutant ctDNA without data on corresponding BRAF status in tumor tissue need to be interpreted with caution [28]. Decrease, and disappearance of ctDNA have been shown to be associated with improved PFS [38] and prolonged OS [39]. An impact of decreasing ctDNA on response to treatment has been found in targeted but not in immunotherapies [35], and in adoptive T-cell transfer a complete clearance after an early peak was associated with better responses [39].…”
Section: Liquid Biopsy Modalities and Their Clinical Application In Amentioning
confidence: 99%
“…3 Furthermore, a significantly higher PFS was found for patients in whom ctBRAF V600mut became undetectable at some time point after initiation of targeted therapy. 4 From 2012 to 2014, 85 patients from the onco-dermatology department of the Saint-Louis Hospital (Paris, France) presenting unresectable stage III (n=12) or stage IV (n=73) melanoma with BRAF V600E mutated lesions at targeted therapy initiation (BRAF inhibitors, vemurafenib or dabrafenib) were included in this retrospective study after signed informed consent. The cohort included 52 (62%) patients presenting a stage IV m1c melanoma, and 23 (27%) had brain metastasis.…”
mentioning
confidence: 99%